Condensed Matter Systems Exposed to Radiation: Multiscale Theory, Simulations, and Experiment - Solov'yov, Andrey V; Verkhovtsev, Alexey V; Mason, Nigel J; Amos, Richard A; Bald, Ilko; Baldacchino, Gérard; Dromey, Brendan; Falk, Martin; Fedor, Juraj; Gerhards, Luca; Hausmann, Michael; Hildenbrand, Georg; et al. (Chemical reviews, 2024)
This roadmap reviews the new, highly interdisciplinary research field studying the behavior of condensed matter systems exposed to radiation. The Review highlights several recent advances in the field and provides a roadmap for the development of the field over the next decade. Condensed matter systems exposed to radiation can be inorganic, organic, or biological, finite or infinite, composed of different molecular species or materials, exist in different phases, and operate under different thermodynamic conditions. Many of the key phenomena related to the behavior of irradiated systems are very similar and can be understood based on the same fundamental theoretical principles and computational approaches. The multiscale nature of such phenomena requires the quantitative description of the radiation-induced effects occurring at different spatial and temporal scales, ranging from the atomic to the macroscopic, and the interlinks between such descriptions. The multiscale nature of the effects and the similarity of their manifestation in systems of different origins necessarily bring together different disciplines, such as physics, chemistry, biology, materials science, nanoscience, and biomedical research, demonstrating the numerous interlinks and commonalities between them. This research field is highly relevant to many novel and emerging technologies and medical applications.